Development of indicators and analysis of barriers for assessment and prevention of cutaneous graft-versus-host disease after haematopoietic stem cell transplantation in children - YANG Liling; ZHAN Sha; XUE Xiaoyan; CHEN Kai; LIU Qing; WANG Li; WANG Yiyi; WU Meng; LU Qunfeng (Shanghai Jiaotong Daxue xuebao. Yixue ban)
Objective·To gain a comprehensive understanding of the current clinical status of assessment and prevention of cutaneous graft-versus-host disease (GVHD) after haematopoietic stem cell transplantation in children, construct review indicators, analyze obstacles and facilitators in the process of conducting the study in light of clinical reality, and formulate strategies for change.Methods·Utilizing the JBI Evidence-Based Health Care Model as a theoretical guiding framework, the clinical problem was clarified. An evidence-based practice team was established, and a systematic literature search was conducted. The evidence was then evaluated and summarized. Additionally, review indicators were constructed, and review methods were clarified in relation to the evidence. Using the Ottawa Model of Research Use, the three dimensions of evidence change, potential adopters, and practice environment were analyzed for barriers and facilitators, and corresponding strategies were developed.Results·A total of 24 pieces of best evidence were included in the study, comprising five dimensions: skin assessment, assessment of protection, management of adverse skin reactions, medication guidance and follow-up and screening. Twenty-two review indicators were constructed on this basis, of which 14 had an implementation rate of <60% and 10 had an implementation rate of 0%; 8 had an implementation rate of >60% and 6 had an implementation rate of 100.00%. The main obstacles were the lack of relevant training and the absence of a rational management mechanism. The main facilitating factors were reliable sources of evidence and a high level of cooperation from potential stakeholders. Considering the results of the analysis of the implementation rate of the indicators under review and the obstacles, alternative measures were formulated.Conclusion·There is a large gap between the evidence and clinical practice for the assessment and prevention of cutaneous GVHD after paediatric haematopoietic stem cell transplantation. Clinical change should be effectively implemented based on barriers and facilitators.